The Impact of COVID-19 on the UAE Economy Vs. the USA Economy - Al Suwaidi, Saif (2021)
The COVID-19 pandemic has led to negative impacts on different areas and industries. The health impacts of the disease have been profound as characterized by the high number of deaths globally while subjecting the infected to dependence. Concurrently, economies have had to deal with declines resulting from reduced trade and travel in line with the need to control the spread of the disease (Lyocsa et al., 2020). As one of the most developed nations, the United States has better capabilities than other countries in dealing with pandemic-related issues. The study that follows takes a comparative approach in investigating the impact of the pandemic on both the economies of the United Arab Emirates and the United States. Understanding the implications of the problem can influence better management through informed decision-making.